Educating for Unbuilt Futures: AI as a Co-Speculative Partner in Climate-Resilient Architectural Pedagogy - Makakli, Elif Süyük (International Journal of Architectural Engineering Technology, 2025)
Architectural education stands at a critical intersection of accelerating climate crises, technological transformation, and social complexity. At the center of this transition lies Artificial Intelligence (AI)—a defining technology reshaping both design processes and cognitive paradigms. Although AI is becoming increasingly embedded in architectural practice, its pedagogical potential remains predominantly instrumental, often limited to applications in form generation and performance optimization. This study reframes AI as a co-speculative pedagogical partner—a reflective agent capable of nurturing ethical, ecological, and contextually responsive design intelligence. Responding to contemporary challenges such as climate instability, resource scarcity, and spatial inequality, the research aligns with the Sustainable Development Goals (SDGs 4, 11, and 13). A multi-layered qualitative methodology was adopted to: (i) synthesize theoretical perspectives from speculative design, cognitive science, and environmental philosophy; (ii) examine international frameworks (NAAB, RIBA, UNESCO) to understand how AI’s pedagogical dimension is articulated; and (iii) compare traditional studio pedagogies with emerging AI-augmented workflows. Together, these layers construct a reproducible framework for evaluating AI’s educational integration. The findings identify five interconnected competency domains—technological literacy, strategic design thinking, environmental sensitivity, ethical awareness, and collaborative agency—derived from recent studies and international educational frameworks. While these domains resonate with existing institutional standards, they also reveal the need for new pedagogical models that situate AI within broader ecological and ethical objectives. The study argues that AI can function as a medium for contextual intelligence—bridging computational logic with embodied, climate-responsive creativity. The proposed framework reimagines architectural education as a reflective and adaptive ecosystem where AI enhances, rather than replaces, human judgment. It fosters a synergistic dialogue between data-driven reasoning and embodied design intelligence, preparing future architects to act ethically, creatively, and ecologically within complex design environments.